2018
DOI: 10.3389/fimmu.2017.01956
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expansion Potential of Naive Chimeric Antigen Receptor T Cells from Healthy Donors and Untreated Chronic Lymphocytic Leukemia Patients

Abstract: IntroductionTherapy with chimeric antigen receptor T (CART) cells for hematological malignancies has shown promising results. Effectiveness of CART cells may depend on the ratio of naive (TN) vs. effector (TE) T cells, TN cells being responsible for an enduring antitumor activity through maturation. Therefore, we investigated factors influencing the TN/TE ratio of CART cells.Materials and methodsCART cells were generated upon transduction of peripheral blood mononuclear cells with a CD19.CAR-CD28-CD137zeta thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 44 publications
0
87
0
1
Order By: Relevance
“…30 In regard to stimulation, it was shown that addition of IL-7/IL-15 is superior to cultivation of CART cells in the presence of IL-2 in terms of maintenance and survival of lessdifferentiated T cells. [11][12][13] In this study, addition of idelalisib could, even in the presence of IL-7/IL-15, further increase T N and T SCM cell subpopulations within the CART cell product. Another cytokine associated with enhancement of lessdifferentiated T cells is IL-21.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…30 In regard to stimulation, it was shown that addition of IL-7/IL-15 is superior to cultivation of CART cells in the presence of IL-2 in terms of maintenance and survival of lessdifferentiated T cells. [11][12][13] In this study, addition of idelalisib could, even in the presence of IL-7/IL-15, further increase T N and T SCM cell subpopulations within the CART cell product. Another cytokine associated with enhancement of lessdifferentiated T cells is IL-21.…”
Section: Discussionmentioning
confidence: 56%
“…An enrichment of CD8+ T cells and less‐differentiated T cells can be reached by retronectin‐based T cell activation . In regard to stimulation, it was shown that addition of IL‐7/IL‐15 is superior to cultivation of CART cells in the presence of IL‐2 in terms of maintenance and survival of less‐differentiated T cells . In this study, addition of idelalisib could, even in the presence of IL‐7/IL‐15, further increase T N and T SCM cell subpopulations within the CART cell product.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Conditioning chemotherapy is given 2‐7 days prior to T‐cell infusion. The theoretical benefits of conditioning include direct cytotoxic effect against malignancy, depletion of regulatory T cell and other suppressive immune cells and decreased competition for homeostatic cytokines . The optimal conditioning regimen has not been rigorously examined, but clinical experiences from the NCI and FHCRC are instructive.…”
Section: Bridging To Carsmentioning
confidence: 99%